Knockout of the Complex III subunit Uqcrh causes bioenergetic impairment and cardiac contractile dysfunction - Nadine Spielmann; Christina Schenkl; Tímea Komlódi; Patricia da Silva-Buttkus; Estelle Heyne; Jana Rohde; Oana V. Amarie; Birgit Rathkolb; Erich Gnaiger; Torsten Doenst; Helmut Fuchs; Valérie Gailus-Durner; et al. (Mammalian Genome, 2023)
Ubiquinol cytochrome c reductase hinge protein (UQCRH) is required for the electron transfer between cytochrome c 1 and c of the mitochondrial cytochrome bc 1 Complex (CIII). A two-exon deletion in the human UQCRH gene has recently been identified as the cause for a rare familial mitochondrial disorder. Deletion of the corresponding gene in the mouse ( Uqcrh -KO) resulted in striking biochemical and clinical similarities including impairment of CIII, failure to thrive, elevated blood glucose levels, and early death. Here, we set out to test how global ablation of the murine Uqcrh affects cardiac morphology and contractility, and bioenergetics. Hearts from Uqcrh -KO mutant mice appeared macroscopically considerably smaller compared to wildtype littermate controls despite similar geometries as confirmed by transthoracic echocardiography (TTE). Relating TTE-assessed heart to body mass revealed the development of subtle cardiac enlargement, but histopathological analysis showed no excess collagen deposition. Nonetheless, Uqcrh -KO hearts developed pronounced contractile dysfunction. To assess mitochondrial functions, we used the high-resolution respirometer NextGen-O2k allowing measurement of mitochondrial respiratory capacity through the electron transfer system (ETS) simultaneously with the redox state of ETS-reactive coenzyme Q (Q), or production of reactive oxygen species (ROS). Compared to wildtype littermate controls, we found decreased mitochondrial respiratory capacity and more reduced Q in Uqcrh -KO, indicative for an impaired ETS. Yet, mitochondrial ROS production was not generally increased. Taken together, our data suggest that Uqcrh -KO leads to cardiac contractile dysfunction at 9 weeks of age, which is associated with impaired bioenergetics but not with mitochondrial ROS production. Graphical abstract Global ablation of the Uqcrh gene results in functional impairment of CIII associated with metabolic dysfunction and postnatal developmental arrest immediately after weaning from the mother. Uqcrh -KO mice show dramatically elevated blood glucose levels and decreased ability of isolated cardiac mitochondria to consume oxygen (O 2 ). Impaired development (failure to thrive) after weaning manifests as a deficiency in the gain of body mass and growth of internal organ including the heart. The relative heart mass seemingly increases when organ mass calculated from transthoracic echocardiography (TTE) is normalized to body mass. Notably, the heart shows no signs of collagen deposition, yet does develop a contractile dysfunction reflected by a decrease in ejection fraction and fractional shortening.

Discrepancy between GLUT4 translocation and glucose uptake after ischemia - Vlad Zaha; Roland Nitschke; Heike Göbel; Ulrich Fischer-Rasokat; Christoph Zechner; Torsten Doenst (Molecular and Cellular Biochemistry, 2005)

Insulin improves postischemic recovery of function through PI3K in isolated working rat heart - Vlad Zaha; Ieda Francischetti; Torsten Doenst (Molecular and Cellular Biochemistry, 2003)

The role of calcium in the regulation of glucose uptake in isolated working rat heart - Christoph Zechner; Friedhelm Beyersdorf; Torsten Doenst (Molecular and Cellular Biochemistry, 2002)

Ischemic preconditioning in rat heart: No correlation between glycogen content and return of function - Torsten Doenst; Patrick H. Guthrie; Heinrich Taegtmeyer (Molecular and Cellular Biochemistry, 1998)